ANALISIS UJI TANTANG UDANG VANAME (Litopenaeus vannamei) YANG DIBERI BAKTERI PROBIOTIK Bacillus sp. D2.2 DAN EKSTRAK UBI JALAR SEBAGAI SINBIOTIK - Wijayanti, Arlin; Dwinitasari, Nandya; Febriyani, Uun; Harpeni, Esti; Wardiyanto, Wardiyanto (Biospecies, 2018)
In vaname shrimp cultivation system, bacterial disease is a problem that often arises that mainly caused by the bacteria Vibrio sp. Sinbiotic application is one way to prevent disruption of the disease. Sinbiotic is nutritional supplements that made from the combination of probiotic and prebiotic that can provide beneficial effects to the host. This research uses a local sinbiotic of probiotic bacteria Bacillus sp. D2.2, which comes from the traditional ponds in the Mulyosari village, Pasir Sakti district, Lampung Timur Regency, Lampung. Prebiotic that used in this research made from meal extracts of purple sweet potato that had the best capability to support the growth of bacteria probiotic Bacillus sp. D2.2. This research aims to know the effectivity of sinbiotic against the infection of vibriosis againts to vaname shrimp by doing analysis of clinical symptoms and tissue damage post test challenge using bacteria Vibrio harveyi. The results showed that addition sinbiotic gave effect to SR 6,25 %, MTD 13,80 hour, and clinical symptoms and then tissue damage is lower than without the feeding of sinbiotik.